2018
DOI: 10.4314/bajopas.v10i2.30
|View full text |Cite
|
Sign up to set email alerts
|

Yield and yield components of intercropped dual-purpose lablab and cowpea with maize of contrasting maturities

Abstract: Intercropping is a way to intensify agricultural land use. Cowpea is an important crop in the traditional farming systems in northern Nigeria because it serves to provide food and feed. Although lablab has potential to function in these ways, it remains an underutilized crop because among other factors, there is dearth of information on its incorporation into the system by way of intercropping it with the major cereal crops. A field trial was conducted at Samaru (11º 11'N, 07º 38'E, 686 m asl) in northern Guin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…On sandy clay soil in Cameroon, Tchiagam et al (2010) reported 892 kg ha −1 and 1369 kg ha −1 as grain and fodder yields, respectively. Similarly, on loamy soil, Ewansiha et al (2017) found average grain and fodder yields of 1260 kg ha −1 and 2446 kg ha −1 , respectively in Nigeria. The DP cowpeas are grown either in monocropping systems or in association or in rotation with cereals crops (Singh et al, 1997).…”
Section: Performances Of Dual‐purpose Varietiesmentioning
confidence: 92%
“…On sandy clay soil in Cameroon, Tchiagam et al (2010) reported 892 kg ha −1 and 1369 kg ha −1 as grain and fodder yields, respectively. Similarly, on loamy soil, Ewansiha et al (2017) found average grain and fodder yields of 1260 kg ha −1 and 2446 kg ha −1 , respectively in Nigeria. The DP cowpeas are grown either in monocropping systems or in association or in rotation with cereals crops (Singh et al, 1997).…”
Section: Performances Of Dual‐purpose Varietiesmentioning
confidence: 92%